COPPER AND ZINC INDUCED CHANGES IN SOYBEAN (Glycine max (L.) Merr.) - K. Ganesh; P. Sundaramoorthy (Innovations in Agriculture)
Heavy metals are one of the most important pollutants released to the aquatic environment by the various industrial activities. The use of these wastewater for irrigation results accumulation of heavy metals in soil and plants. So, the present investigation deals with the various concentrations (0, 5, 10, 25, 50, 100, 200 and 300 mg/l) of copper and zinc on germination studies of soybean. The different concentrations of copper and zinc were used for germination studies. The seedlings were allowed to grow upto seven days. The studied morphological traits increased at 5 mg/l concentration and these parameters are gradually decreased with the increase of copper and zinc concentrations.